Introductory Mathematics and Statistics for Islamic Finance - Mirakhor, Abbas (Singapore : Wiley, 2014)
A unique primer on quantitative methods as applied to Islamic finance Introductory Mathematics and Statistics for Islamic Finance + Website is a comprehensive guide to quantitative methods, specifically as applied within the realm of Islamic finance. With applications based on research, the book provides readers with the working knowledge of math and statistics required to understand Islamic finance theory and practice. The numerous worked examples give students with various backgrounds a uniform set of common tools for studying Islamic finance. The in-depth study of finance requires a strong.
Mathematics. Elementary Mathematics -- Functions and Models -- Differentiation and Integration of Functions -- Partial Derivatives -- Logarithm, Exponential, and Trigonometric Functions -- Linear Algebra -- Differential Equations -- Difference Equations -- Optimization Theory -- Linear Programming -- Statistics. Introduction to Probability Theory: Axioms and Distributions -- Probability Distributions and Moment Generating Functions -- Sampling and Hypothesis Testing Theory -- Regression Analysis -- Time Series Analysis -- Nonstationary Time Series and Unit-Root Testing -- Vector Autoregressive Analysis (VAR) -- Co-Integration: Theory and Applications -- Modeling Volatility: ARCH-GARCH Models -- Asset Pricing under Uncertainty -- The Consumption-Based Pricing Model -- Brownian Motion, Risk-Neutral Processes, and the Black-Scholes Model.
Includes bibliographical references and index.
Print version record.
Keywords: Business mathematics -- Islamic countries; Finance -- Statistics; Finance, Public -- Islamic countries; SOCIAL SCIENCE -- Essays; SOCIAL SCIENCE -- Reference; Business mathematics; Finance; Finance, Public; Islamic countries; Electronic books; Statistics